Incidence of HCV induced—Esophageal varices in Egypt: Valuable knowledge using data mining analysis. Issue 4 (January 2017) - Abdel-aty, Mahmoud; Fouad, Mahmoud; Sallam, Mohammad M.; Elgohary, Elsayed A.; Ismael, Ali; Nawara, Abdallah; Hawary, Baha; Tag-Adeen, Mohammed; Khaled, Salama
Abstract : Abstract: Esophageal varices is one of the most important comorbidity related liver cirrhosis, patients usually presented with hematemesis, melena, or both, ultimately 20% is the mortality during the first attack, hence we aimed to investigate the incidence of such esophageal varices related chronic Hepatitis C virus (HCV) in randomized Egyptian population. One thousand eighteen Egyptian patients, aged between 17 and 58 years, positive for Hepatitis C virus genotype 4 (HCV-4) by enzyme linked immunosorbent assay Ab and HCV RNA-polymerase chain reaction were screened for the presence of esophageal varices. Incidence of esophageal varices was 62.3%; 635 patients, those with large Esophageal varices (LEVs) was 47.4%; 301 patients. Model for end-stage liver disease (MELD) score has not been significantly improved post variceal band ligation (VBL). Using 2D U/S was useful for EVs prediction. Incidence of esophageal varices in HCV Egyptian patients still high, valuable knowledge would be helpful in clinical field have been discovered by data mining computational intelligent analysis using in practical medicine to improve overall health care.